Analysis of the Influence of Life Cycle, Investment Opportunity Set, Profitability, Leverage, and Free Cash Flow Equity on Dividend Policy in Property, Real Estate, and Building Construction Companies on the Indonesia Stock Exchange - Nur Aisyah Fitri; Khaira Amalia Fachrudin; Syahyunan (Indonesian Journal of Business Analytics, 2025)
The purpose of this study is to examine how dividend policy is affected by life cycle, investment opportunity set, profitability, leverage, and free cash flow equity in companies that are listed on the Indonesia Stock Exchange and are involved in property, real estate, and building construction. In this study, the Panel Data Regression Model with Random Effect Model is used. The findings indicate that life cycle has a significant and beneficial impact on dividend policy, whereas leverage has a significant and negative impact at a significance level of 0.05. At a significance level of 0.1, profitability, on the other hand, exhibits a positive and significant influence. However, there is a slight but favorable impact on dividend policy from free cash flow equity and investment opportunity set.